1970
DOI: 10.4314/majohe.v11i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Justifications for Undertaking Marketing Orientation Studies in Higher Learning Institutions in Tanzania

Abstract: This paper was written with the major aim of presenting a number of issues which justify the undertaking of marketing orientation studies in Tanzania Higher Learning Institutions (HLIs). It was also the intention of the authors to give a brief picture of marketing practice in Tanzania environment and on the higher learning institutions. The information used in this paper was mainly collected through review of literatures on articles which focused on marketing orientation and higher learning institutions. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to nearly identical results from another study, South Africa, Egypt, Tunisia, and Nigeria were the top five nations in terms of research outputs (Confraria & Godinho, 2015). The literature suggests that academic staff performance is impacted by upholding ethical values (Muya & Tundui, 2020;Katundano, 2019). However, ethical guidance has not been studied much as a predictor for academic staff teaching performance.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…According to nearly identical results from another study, South Africa, Egypt, Tunisia, and Nigeria were the top five nations in terms of research outputs (Confraria & Godinho, 2015). The literature suggests that academic staff performance is impacted by upholding ethical values (Muya & Tundui, 2020;Katundano, 2019). However, ethical guidance has not been studied much as a predictor for academic staff teaching performance.…”
Section: Introductionmentioning
confidence: 94%
“…This suggests that a leader's moral governance affects followers' behavior in the classroom. In addition, the study by Muya and Tundui (2020) on the strategies for improving the performance of HLIs in Tanzania stated that HLI staff members must observe ethical values for better employee' teaching performance. These findings are in line with the study by Katundano (2019) on Rebuilding Ethical Leadership in African Universities, which revealed that ethical principles are key principles for universities promoting staff's performance in teaching, research, and consultancy.…”
Section: Source: Data Analysismentioning
confidence: 99%
“…To improve the situation, HLIs need to be market-oriented by ensuring excellent, quality service delivery by improving service facilities, learning to understand industry requirements and customer characteristics, and keeping up with the competition in the industry. This, according to Muya and Tundui (2020), will make HLIs more competitive domestically and internationally. Likely, HLIs, as a significant component of the service sector, need to apply different strategies that will assure them of positive WoM.…”
Section: Introductionmentioning
confidence: 99%